2013
DOI: 10.1016/j.neuroimage.2013.04.115
|View full text |Cite
|
Sign up to set email alerts
|

Multiple synergistic effects of emotion and memory on proactive processes leading to scene recognition

Abstract: 21Visual scene recognition is a proactive process through which contextual cues and top-down 22 expectations facilitate the extraction of invariant features. Whether the emotional content of the 23 scenes exerts a reliable influence on these processes or not, however, remains an open question. 24Here, topographic ERP mapping analysis and a distributed source localization method were used 25 to characterize the electrophysiological correlates of proactive processes leading to scene 26 recognition, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Research has shown that positivity offset (as well as negativity bias) can be generalized across different kinds of stimuli (Norris, Larsen, Crawford, & Cacioppo, 2011), is temporally stable and trait-like consistent (Ito & Cacioppo, 2005), and can be used as a theoretical construct to interpret serotonergic function in healthy and clinical populations (Ashare, Norris, Wileyto, Cacioppo, & Strasser, 2013;Carver, Johnson, & Joormann, 2009;Gollan et al, 2016). During our task, positivity offset may have outweighed negativity bias because of the absence of proximal environmental danger which, in turn, promoted exploration (Ito & Cacioppo, 2005;Schettino, Loeys, Bossi, & Pourtois, 2012;Schettino, Loeys, Delplanque, & Pourtois, 2011;Schettino, Loeys, & Pourtois, 2013). Furthermore, participants were probably inclined to thoroughly examine images carrying intrinsically rewarding information also because these pictures likely matched their motivational dispositions (Byrne & Eysenck, 1993;Niedenthal, Halberstadt, & Setterlund, 1997;Niedenthal & Setterlund, 1994;Raila, Scholl, & Gruber, 2015).…”
Section: Pleasant Information Is Prioritized In Early Visual Cortexmentioning
confidence: 97%
“…Research has shown that positivity offset (as well as negativity bias) can be generalized across different kinds of stimuli (Norris, Larsen, Crawford, & Cacioppo, 2011), is temporally stable and trait-like consistent (Ito & Cacioppo, 2005), and can be used as a theoretical construct to interpret serotonergic function in healthy and clinical populations (Ashare, Norris, Wileyto, Cacioppo, & Strasser, 2013;Carver, Johnson, & Joormann, 2009;Gollan et al, 2016). During our task, positivity offset may have outweighed negativity bias because of the absence of proximal environmental danger which, in turn, promoted exploration (Ito & Cacioppo, 2005;Schettino, Loeys, Bossi, & Pourtois, 2012;Schettino, Loeys, Delplanque, & Pourtois, 2011;Schettino, Loeys, & Pourtois, 2013). Furthermore, participants were probably inclined to thoroughly examine images carrying intrinsically rewarding information also because these pictures likely matched their motivational dispositions (Byrne & Eysenck, 1993;Niedenthal, Halberstadt, & Setterlund, 1997;Niedenthal & Setterlund, 1994;Raila, Scholl, & Gruber, 2015).…”
Section: Pleasant Information Is Prioritized In Early Visual Cortexmentioning
confidence: 97%
“…Research has shown that positivity offset (as well as negativity bias) can be generalized across different kinds of stimuli (Norris, Larsen, Crawford, & Cacioppo, 2011), is temporally stable and trait-like consistent (Ito & Cacioppo, 2005), and can be used as a theoretical construct to interpret serotonergic function in healthy and clinical populations (Ashare, Norris, Wileyto, Cacioppo, & Strasser, 2013;Carver, Johnson, & Joormann, 2009;Gollan et al, 2016). During our task, positivity offset may have outweighed negativity bias because of the absence of proximal environmental danger which, in turn, promoted exploration (Ito & Cacioppo, 2005;Schettino, Loeys, Bossi, & Pourtois, 2012;Schettino, Loeys, Delplanque, & Pourtois, 2011;Schettino, Loeys, & Pourtois, 2013). Furthermore, participants were probably inclined to thoroughly examine images carrying intrinsically rewarding information also because these pictures likely matched their motivational dispositions (Byrne & Eysenck, 1993;Niedenthal, Halberstadt, & Setterlund, 1997;Niedenthal & Setterlund, 1994;Raila, Scholl, & Gruber, 2015).…”
Section: Pleasant Information Is Prioritized In Early Visual Cortexmentioning
confidence: 98%
“…Separately for each ERP component, positive and negative feedback were compared during the exact same interval (with a mean activity) as used for the standard ERP data analysis (see above). We used paired samples t tests performed on the log-transformed data, and, as in our previous studies, we set the level of significance for all source localization analyses at p < .01 (see also Schettino, Loeys, Delplanque, & Pourtois, 2011;Schettino, Loeys, & Pourtois, 2013).…”
Section: Source Localizationmentioning
confidence: 99%